Virtual reality vs. real world: 3D kinematic analysis in table tennis - Škopek, M.; Hnízdil, J.; Ševcovic, J.; Heidler, J.; Ptácek, M. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
Introduction This study conducts a comparative analysis of packing rate key performance indicators across top football leagues in South Africa, England, Spain, Germany and the UEFA Champions League. Packing rate, a novel metric developed by Impect GmbH measures the effectiveness of player actions in bypassing opponent players, offering a deeper insight into the game into the match`s dynamics (Goes, 2019). The research aimed to evaluate its comparative applicability across different leagues using packing rate metrics.